ASSESSMENT OF THE IMPACT OF PERCEIVED CORRUPTION ON ECONOMIC GROWTH USING THE GLS MODEL - Vasko Kelić; Ivana Ostojić; Predrag Jovanović (Acta Economica)
Researchers not only dissent on what effect corruption has on economic growth but also whether this effect holds in different institutional contexts. Some economists argue that corruption can stimulate economic growth in environments with poor governance and ineffective institutions (such as those in the Western Balkans region), while others suggest otherwise. This paper aims to investigate the relationship between perceived corruption and GDP per capita change in ten European countries from 2012 to 2021. Our goal is to examine whether non-EU Western Balkans countries, characterised by ineffective governance and underdeveloped institutions, are more or less sensitive to corruption compared to more developed European countries. To obtain robust estimates, we employ a feasible generalised least squares estimation method (GLS). Besides showing a negative effect on the full sample, our analysis confirms different intensities of corruption impact on economic growth under the two governance regimes. The research suggests that the negative effect of corruption is stronger in countries with developed institutions (EU countries). We find that the impact of corruption on economic growth in such countries amounts to up to 1.94 percent drop in GDP per capita after a one-unit rise in corruption level, while the one in non-EU WB countries stands at a maximum of 0.75 percent decrease. Compared to earlier findings, ours are characterised by the focus on Western Balkans countries, the inclusion of more recent data and a more comprehensive pre-estimation analysis.